The applications of functional materials-based nano-formulations in the prevention, diagnosis and treatment of chronic inflammation-related diseases - Wang, Jingjing; Ni, Rui; Jiang, Tingting; Peng, Dan; Ming, Yue; Cui, Hongjuan; Liu, Yao (Frontiers in Pharmacology, 2023)
Chronic inflammation, in general, refers to systemic immune abnormalities most often caused by the environment or lifestyle, which is the basis for various skin diseases, autoimmune diseases, cardiovascular diseases, liver diseases, digestive diseases, cancer, and so on. Therapeutic strategies have focused on immunosuppression and antiinflammation, but conventional approaches have been poor in enhancing the substantive therapeutic effect of drugs. Nanomaterials continue to attract attention for their high flexibility, durability and simplicity of preparation, as well as high profitability. Nanotechnology is used in various areas of clinical medicine, such as medical diagnosis, monitoring and treatment. However, some related problems cannot be ignored, such asincluding various cytotoxic and worsening inflammation caused by the nanomaterials themselves. This paper provides an overview of functional nanomaterial formulations for the prevention, diagnosis and treatment of chronic inflammation-related diseases, with the intention of providingintending to provide some reference for the enhancement and optimization of existing therapeutic approaches.